Estonia's digital diplomacy: Nordic interoperability and the challenges of cross-border e-governance - Alex Hardy (Internet Policy Review, 2024)
Estonia has long been held as a leading example of e-Governance. Estonia's ubiquitous e- Governance is enabled by the X-Road, an open-source data exchange layer that allows the secure exchange of data. This paper explores the X-Road integration between Estonia, Finland, the Faroe Islands, the Åland Islands, and Iceland. Having been originally pioneered and implemented by Estonia and developed by the Estonian Information System Authority (RIA), X-Road is increasingly attractive to other nations drawn to the digital services it can enable. This paper argues that the cross-border implementation of the X-road, pioneered by Estonia, is a form of digital diplomacy - an opportunity to extend influence and shape e-norms among geopolitically like-minded partners. Prior conceptions of digital diplomacy have focused on citizen engagement - often specifically on the use of Twitter or other social media platforms for public outreach. This study suggests, however, that our understanding of digital diplomacy ought to extend beyond such undoubtedly important interpretations to also encompass the use of technology in developing closer diplomatic relations. The study utilises a series of semi-structured interviews with government officials and private sector actors to support its arguments around the diplomatic and geopolitical implications of e- Governance as a diplomatic tool.
Keywords: 300; Estonia; E-government; Digital diplomacy; Innovation; Cross-border e-governance